THE OCCURRENCE OF CRITICAL ABNORMAL GRAIN-GROWTH IN SUPER PURITY ALUMINUM AND HIGH-PURITY COPPER WAR-HEAD CONES - CIGDEM, M (CARL HANSER VERLAG, 1994)
The response to low cold deformation and annealing of 99.99% purity aluminium and 99.92% copper with a wide range of initial grain sizes has been investigated. Particularly, variations in the values of the critical strain, subsequent selective abnormal (maximum) grain growth and the recrystallised grain size have been correlated with the initial grain size, the final annealing temperature and the deformation. An increase in the maximum grain sizes and lower values of critical strain were observed by decreasing the initial grain size and by increasing the annealing temperature. Decreasing initial grain size produces smaller recrystallised grain size at moderate strains which exceed the critical strain range. Also examined is the recrystallisation behaviour of the specimens taken from different parts of a commercially produced high purity copper cone. Lower values of grain sizes were obtained in the thin wall section of the component where the amount of working is apparently maximum. Whereas coarser grains and higher recrystallisation temperatures were found to be associated with the apex of the cones where the deformation is minimum as confirmed by hardness results.
Keywords: CASTING PRACTICE; STRAIN; Metallurgy & Metallurgical Engineering